2016
DOI: 10.3748/wjg.v22.i17.4307
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments and innovations in gastric cancer

Abstract: Gastric cancer has an important place in the worldwide incidence of cancer and cancer-related deaths. It can metastasize to the lymph nodes in the early stages, and lymph node metastasis is an important prognostic factor. Surgery is a very important part of gastric cancer treatment. A D2 lymphadenectomy is the standard surgical treatment for cT1N+ and T2-T4 cancers, which are potentially curable. Recently, the TNM classification system was reorganized, and the margins for gastrectomy and lymphadenectomy were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 118 publications
0
61
0
Order By: Relevance
“…Knockout of M1.HpyAVI largely prevents the growth of H. pylori [20]. Importantly, H. pylori is involved in 90% of all gastric malignancies [19]. Appropriate antibiotic regimens could successfully cure gastric diseases caused by H.pylori infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockout of M1.HpyAVI largely prevents the growth of H. pylori [20]. Importantly, H. pylori is involved in 90% of all gastric malignancies [19]. Appropriate antibiotic regimens could successfully cure gastric diseases caused by H.pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is a major pathogen of gastritis and peptic ulcer diseases as well as a cancer-causing factor for gastric cancer. H. pylori is involved in 90% of all gastric malignancies, infecting nearly 50% of the world's population and is the most crucial etiologic agent for gastric adenocarcinoma [19]. H. pylori strains possess a few R-M systems like other bacteria to function as defensive systems.…”
Section: Introductionmentioning
confidence: 99%
“…To provide data that will enable the development of novel therapeutic strategies, it is crucial to elucidate the molecular mechanisms that promote the migration and invasion properties of gastric cancer. Metastasis is defined as the process of dissemination of cancer cells from their origin to a distant organ, a complex process involving several stages, which are as follows: i) The activation of EMT; ii) local invasion; iii) intravasation; iv) the ability to survive in the bloodstream; v) extravasation, whereby tumor cells exit the bloodstream; and vi) establishment of tumor cells in the tissues of a distant organ (16). EMT is a multistage reprogramming process that is also important in the physiological process of embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Her-2 at the protein and/or mRNA level is detected in a variable percentage of cases, depending on the tumor (27)(28)(29). Furthermore, unlike breast cancer, previous studies have reported inconsistent findings regarding the prognostic role of Her-2 in gastric cancer (30)(31)(32). A previous study demonstrated that patients with intestinal-type and well-differentiated gastric cancer have a higher rate of Her-2 positivity than patients with diffuse-type and poorly-differentiated cancer (29).…”
Section: Discussionmentioning
confidence: 99%